Credentialing and certification: Overview, science, and impact on policy, regulation, and practice. (30th September 2021) - Chappell, Kathy B.; Howard, Matthew S.; Lundmark, Vicki; Ivory, Cathy
Abstract: Aim: To engage the global nursing community in sharing knowledge, experiences, and lessons learned about credentialing of individual nurses to improve nursing practice, patient safety, and quality of care. Background: Although the United States has a long and robust history of credentialing individual nurses, the opportunity exists to expand the dialogue globally, and is supported by globally focused governing bodies who call for increased or expanded investment in nursing certification and credentialing. Foundational work to define and operationalize certification for research purposes and develop an administrative home for stakeholders interested in certification can be leveraged by countries and regions globally. Existing frameworks for credentialing research may be used to drive theory‐based research in the future. Sources of Evidence: PubMed, International Council of Nurses, National Academies of Sciences, Engineering, and Medicine, World Health Organization, American Nurses Association, American Nurses Credentialing Center, and the authors' own experiences. Discussion: Credentialing as a form of self‐governance, as a method for public protection, and as a foundational element in the increasingly new forms of healthcare delivery is intensifying in importance. Credentials provide an opportunity to evaluate relationships between key elements such as nursing practice, environments where nursing care is delivered, and nursing programs with outcomes of interest for the profession such as safety, quality of care, and patient outcomes. Conclusions: Establishing rigorous credentials for nurses demonstrates a commitment to excellence. Credentialing frameworks that are universally applied could enable nurses to move seamlessly across geographic boundaries, permit regulators and employers of nurses to have a common set of standards and expectations, and ensure a level of competency for nursing practice that can be interpreted and trusted by various stakeholders. Implications for Nursing Policy: Policymakers have a pivotal role in advancing credentialing in nursing worldwide. Countries developing credentialing programs in nursing need to study their results to help inform how practice might be required to change over time.